Determination of joint loads using new sensate scaffolds for regenerating large cartilage defects in the knee. Issue 6 (15th April 2016) - Szivek, John A.; Ruth, John T.; Heden, Greg J.; Martinez, Michael A.; Diggins, Nicklaus H.; Wenger, Karl H.
Abstract: Two complete unicondylar surface replacement scaffold designs to support tissue‐engineered cartilage growth that utilized adult endogenous stem cells were 3D printed and tested in a dog stifle model. Integrated rosette strain gauges were calibrated and used to determine shear loading within stifle joints for up to 12 months. An activity index that compared extent of daily activity with tissue formation showed differences in the extent and quality of new tissue with the most active animal having the most new tissue formation. Shear loads were highest early and decreased with time indicating that cartilage tissue formation begins while tissues experience high shear loads and continues as the loads decrease toward normal physiological levels. Scaffolds with biomimetic support pegs facilitated the most rapid bone ingrowth and were noted to have more cartilage formation with better quality cartilage as measured using both indentation testing and histology. Comparison of implant placement depth to previous studies suggested that placement depth affects the amount of tissue formation. This study provides measurements of loading patterns and cartilage regeneration on a complete medial condylar surface replacement that can be used for preclinical testing of a tissue engineering approach for the most common form of early stage osteoarthritis, unicondylar disease. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1409–1421, 2017.